Sundin ang linya using line and color to aid in the wayfinding of patients and their guardians at the research institute of tropical medicine - Melo, Katrina Maria Nievera
Getting lost in a hospital is an unpleasant experience. We blame ourselves for getting lost and not finding our own way, but too often it is not our fault. An ineffective wayfinding system may be to blame. In a highly stressful situation, signs are often overlooked, which makes finding the right room more difficult and more time consuming. In the case of emergency situations, time is a highly crucial aspect because the longer it takes a patient to get treatment, the more serious his/her condition can become. In worst cases. the time it takes to get to the proper room for treatment could mean the difference between life and death. Being able to find your way within a healthcare facility with the least amount of time is critical. This thesis aims to aid patients and their guardians in the wayfinding in hospitals and in effect, make the process more efficient by incorporating visual cues into the wayfinding system. My research has shown that a combination of both pictographics and typographics is the most effective way of presenting wayfinding information. Along with this, I found that the line type of directional signage is also an effective way of directing people to their destinations. By incorporating both of these along with color, a wayfinding system can be created that will make finding your way around hospitals more efficient, less stressful, and provide a more pleasant hospital experience.